Overview of nursing problems in patients undergoing hemodialysis using Virginia Henderson's nursing theory approach: A descriptive study - Aniska Indah Fari; Veroneka Yosefpa Windahandayani (School of Health Sciences Al-Ma'arif, 2026)
Background: Patients undergoing hemodialysis often experience complex nursing problems involving physiological, psychological, social, and spiritual dimensions. A comprehensive nursing assessment is therefore essential to identify patients’ basic needs and guide holistic care. Virginia Henderson’s nursing theory provides a relevant framework for assessing 14 fundamental human needs among patients with chronic kidney disease receiving hemodialysis. Objective: This study aimed to describe nursing problems among patients undergoing hemodialysis using Virginia Henderson’s nursing theory approach. Methods: This study employed a quantitative descriptive design. The study was conducted in the Hemodialysis Unit of RSUD Siti Fatimah Az-Zahrah Palembang from June to July 2025. A total sampling technique was used, involving 35 patients who met the inclusion criteria, namely undergoing routine hemodialysis twice weekly, having received hemodialysis for more than three months, and using an arteriovenous fistula. Data were collected through interviews, physical examination, and nursing documentation review using an observation sheet based on Virginia Henderson’s 14 basic human needs. Nursing problems were identified according to the Indonesian Nursing Diagnosis Standards. Data were analyzed descriptively and presented as frequencies and percentages. Results: The mean age of respondents was 52.17 years, with a standard deviation of 11.947. Most respondents were female (51.4%), and 40% had undergone hemodialysis for more than 24 months. The most prevalent nursing problem was hypervolemia, found in all respondents (100%), followed by ineffective breathing pattern (80%), fatigue (80%), impaired urinary elimination (72%), ineffective role performance (23%), hopelessness (20%), ineffective health management (17%), and disturbed sleep pattern (17%). No nursing problem was identified in relation to worship according to personal belief. Conclusion: Patients undergoing hemodialysis experience multiple nursing problems, predominantly related to fluid balance, respiratory function, fatigue, elimination, and psychosocial role performance. Virginia Henderson’s nursing theory offers a comprehensive framework for identifying basic human needs and strengthening holistic, patient-centered nursing care in hemodialysis units.